2019
DOI: 10.1200/jop.18.00595
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Avoidable Hospital Readmissions in Patients With Advanced Cancer

Abstract: PURPOSE: Patients with cancer often prefer to avoid time in the hospital; however, data are lacking on the prevalence and predictors of potentially avoidable readmissions (PARs) among those with advanced cancer. METHODS: We enrolled patients with advanced cancer from September 2, 2014, to November 21, 2014, who had an unplanned hospitalization and assessed their patient-reported symptom burden (Edmonton Symptom Assessment System) at the time of admission. For 1 year after enrollment, we reviewed patients’ heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 38 publications
(50 reference statements)
0
20
0
2
Order By: Relevance
“…These are important findings, indicating as in previous studies, that family caregivers perform tasks similar to trained healthcare professionals (Ullgren et al, 2018). Previous research has revealed both heavy burden on family caregivers as well as the challenge of living alone during cancer treatment (Johnson et al, 2019; Lash et al, 2017). One third of the patients in our study were living alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are important findings, indicating as in previous studies, that family caregivers perform tasks similar to trained healthcare professionals (Ullgren et al, 2018). Previous research has revealed both heavy burden on family caregivers as well as the challenge of living alone during cancer treatment (Johnson et al, 2019; Lash et al, 2017). One third of the patients in our study were living alone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on cancer healthcare utilisation, mostly focus on end‐of‐life (EoL) care and/or advance stage disease. Unplanned care is an indicator to evaluate healthcare utilisation (Frolich et al, 2008) and may be impacted by diagnosis (Henson et al, 2018), symptom burden (Johnson et al, 2019), co‐morbidity (Kidane et al, 2018) and socioeconomic factors (Henson et al, 2018). Aspects of healthcare utilisation have been used as indicators to demonstrate how well healthcare systems are integrated and structured (BLOCKS: tools & Methodologies to assess integrated care in Europe, 2017; Cortis et al, 2017; Shaw, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon admission (within 5 days of hospitalization), we obtained informed consent and asked patients to complete a symptom burden questionnaire. 16,17,28,32,33 For this study, we used body composition data obtained from routine clinical CT scans. 34,35 The Dana-Farber/Harvard Cancer Center Institutional Review Board approved this study (body composition analysis was conducted as part of a secondary analysis, and the board waived the need to obtain additional consent to access CT scans).…”
Section: Study Proceduresmentioning
confidence: 99%
“…The American Society of Clinical Oncology (ASCO) has suggested a number of quality indicators for EOL care: no more than one emergency department (ED) visit during the last month of life, pain assessment, not dying in the hospital, no intensive care unit admission during the last 30 days of life, enrolment in hospice for a meaningful length of time, and no chemotherapy administered within the last 2 weeks of life [18]. Several studies have shown inadequacies in the quality of EOL care, characterized by late delivery [19], unplanned hospitalization [20][21][22], and aggressive care such as non-beneficial medical treatments or interventions [23]; however, this differs substantially across cancer diagnoses [24]. One study indicated that surgically-treated patients receive significantly less hospice care in the last year of life compared with medically-treated patients [25], while another demonstrated that patients undergoing resection are less likely to enrol in hospice early and more likely to be admitted to an acute-care hospital in the last month of life [26].…”
Section: Introductionmentioning
confidence: 99%